Ameliorative effects of Kyung-Ok-Ko and its mixture with Pueraria lobata Ohwi on postmenopausal osteoporosis by promoting phytoestrogenic activity in rats - Kim, Minseo; Kim, Hyun-Sook; Oh, Joohee; Zhou, Xiangqin; Ahn, SongHee; Koo, Youngtae; Kim, Hyun-Jung; Jang, Jiwon (Frontiers in Nutrition, 2023)
Kyung-Ok-Ko (KOK) is a popular traditional medicine used as a natural alternative to hormone replacement therapy for treating postmenopausal symptoms in Asia. Pueraria lobata Ohwi (P. lobata) is rich in isoflavones and has been traditionally used in combination with other herbs to produce synergistic and pharmaceutical effects via a multi-target approach for disease treatment. We aimed to investigate the phytoestrogenic effects of KOK extract against postmenopausal symptoms in ovariectomized (OVX) rats and confirm its efficacy by mixing KOK and P. lobata extracts. OVX rats were daily oral administrated with KOK and KOK + P. lobata mixture extracts (300–400 mg/kg) and their body weight and tail temperature were monitored for 12 weeks. The biochemical parameters, estradiol levels, and bone turnover markers were measured in the serum samples. Moreover, the estrogen receptor, ER-α and ER-β expression in the uterus and the uterus morphology were evaluated. AMPK, ATG1/ULK1, and mTOR protein expression in the liver were assessed. The 12-week treatment with KOK and KOK + P. lobata mixture extracts did not cause liver damage or hormonal changes in the OVX rats. The treatments reduced the high lipid accumulation-related body weight gain and the tail temperature increase that was induced by ovariectomy. Further, it exhibited protective effects against hyperlipidemia and osteoporosis. No significant difference was observed in uterine weight compared to the OVX-treated group, while endometrial thickness reduction inhibition was observed due to ovariectomy. The bone markers, especially bone mineral density (BMD) and serum osteocalcin levels, significantly decreased in OVX rats, increased with the treatments. Western blotting analysis showed that ER-α and ER-β were not expressed in the treated rats, whereas these proteins were expressed in Sham-operated rats. No significant differences in the phosphorylation of AMPK were observed; however, the ATG1/ULK1 and mTOR protein phosphorylation levels were upregulated and downregulated in the treated rats compared to those of OVX rats, respectively. This is the first in vivo study observing the efficacy and synergistic effects of the mixture of KOK and P. lobata. Our results suggest the potential of KOK and KOK + P. lobata mixture as an alternative therapy for alleviating menopausal symptoms.